2014
DOI: 10.1021/bi500744q
|View full text |Cite
|
Sign up to set email alerts
|

Structured Cyclic Peptides That Bind the EH Domain of EHD1

Abstract: EHD1 mediates long-loop recycling of many receptors by forming signaling complexes using its EH domain. We report the design and optimization of cyclic peptides as ligands for the EH domain of EHD1. We demonstrate that the improved affinity from cyclization allows fluorescence-based screening applications for EH domain inhibitors. The cyclic peptide is also unusually well-structured in aqueous solution, as demonstrated using nuclear magnetic resonance-based structural models. Because few EH domain inhibitors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…This makes it very challenging to predictively design specific cross-links to stabilize a desired loop structure. Currently, identifying the proper linker chemistry, length, and positioning can only be done in an iterative process (Berthelot, Gonçalves, Laïn, Estieu-Gionnet, & Déléris, 2006; Cudic, Wade, & Otvos, 2000; Hayouka et al, 2012; Kamens, Eisert, Corlin, Baleja, & Kritzer, 2014; Qvit et al, 2009). One way to accelerate, this process is to introduce diverse conformational constraints at a late stage of synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it very challenging to predictively design specific cross-links to stabilize a desired loop structure. Currently, identifying the proper linker chemistry, length, and positioning can only be done in an iterative process (Berthelot, Gonçalves, Laïn, Estieu-Gionnet, & Déléris, 2006; Cudic, Wade, & Otvos, 2000; Hayouka et al, 2012; Kamens, Eisert, Corlin, Baleja, & Kritzer, 2014; Qvit et al, 2009). One way to accelerate, this process is to introduce diverse conformational constraints at a late stage of synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This approach may offer a way to specifically tune ion channel trafficking to tune cardiac excitability in disease. Indeed, this potential has sparked the active development of EHD inhibitors (63,64). We have previously demonstrated that in vitro EHD3 overexpression is sufficient to tune cell excitability (7), suggesting that targeting endosomal transport may be a feasible approach.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cyclic NPF-containing peptides bind to the N-terminal EH domain with higher affinities than the linear ones (Yamabhai et al, 1998;de Beer et al, 2000). And a new cyclic peptide designed for the EHD1 EH domain has obtained nearly 4-fold improvement in affinity in contrast to a typical linear peptide (Kamens et al, 2014). Usually, the β-turn conformation that is adopted by the NPF motif of bound state was well stabilized in these cyclic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, just as in the observation of Kim et al (2001), the rigid cyclic peptide may induce larger conformational changes of its protein partner, slow the association rate, and thus get a lower affinity. Weaker binding affinities were also observed when increasing or decreasing the ring size of a good cyclic peptide (Kamens et al, 2014). Therefore, how to design a specific cyclic peptide with an appropriate conformation is a big challenge for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation